SAT0082 Physical Activity and Rheumatoid Arthritis: Results from QUEST-RA Moroccan Study. (23rd January 2014) - El Kabbaj, S.; rkain, H.; Benslama, I.; lakhdar, T.; Znat, F.; Benbrahim, L.; Benchekroun, B.; Allali, F.; Hajjaj-Hassouni, N.
Abstract : Background: Regular physical activity is associated with decreased morbidity and mortality. Traditionally, patients with rheumatoid arthritis (RA) have been advised to limit physical exercise. Objectives: to Assess the impact of rheumatoid arthritis on physical activity. Methods: The Questionnaires in Standard Monitoring of Patients with Rheumatoid Arthritis (QUEST-RA) is a cross-sectional study that includes a self-report questionnaire and clinical assessment of non selected consecutive outpatients with RA who are receiving usual clinical care. Frequency of physical exercise (>or=30 minutes with at least some shortness of breath, sweating) is queried with 4 response options: >or=3 times weekly, 1-2 times weekly, 1-2 times monthly, and no exercise. Results: The total of 1129 patients were enrolled: 87, 3% were women, the mean age was 48 years, and the mean disease duration was 6 years. Only 2, 8% of all patients reported physical exercise>or=3 times weekly. The majority of the patients were physically inactive with no regular weekly exercise: >80. Physical inactivity was associated with disease duration, higher levels of disease activity, pain, morning stiffness and fatigue. Conclusions: This study provided the evidence that the physical inactivity rates remain high among people with RA during this millennium. The rheumatologist should motivate patients to increase physical activity levels. Disclosure of Interest: None Declared